Pelatihan Membaca Dan Menghitung Cepat Untuk Anak Kelas 1 SDN 067691 Dalam Kegiatan Kampus Mengajar - Siti Safitri; Fajar Utama Ritonga (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Elementary school education (SD) is the basic level for students in pursuing education. Elementary school education is the education of children from the age of 7 to 13 years of primary school education for 6 years, as education at the basic level that is developed in accordance with educational units, regional potential, and socio-culture. In elementary school education at SD Negeri 067691 most of the 1st grade students were not good at reading and counting, because they had thoughts of continuing to play rather than studying, some of them were not sent to kindergarten, and their parents sometimes did not monitor their children in learning process due to being busy at work. Of course this is a problem, especially in the teaching and learning process. From these problems I created the Speed Reading and Fast Counting Training program. The Speed Reading and Fast Counting Training for 1st grade students at SD Negeri 067691 aims to make 1st graders able to read fluently and be good at counting.